2021
DOI: 10.1007/s10856-020-06486-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone-like ceramic scaffolds designed with bioinspired porosity induce a different stem cell response

Abstract: Biomaterial science increasingly seeks more biomimetic scaffolds that functionally augment the native bone tissue. In this paper, a new concept of a structural scaffold design is presented where the physiological multi-scale architecture is fully incorporated in a single-scaffold solution. Hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP) bioceramic scaffolds with different bioinspired porosity, mimicking the spongy and cortical bone tissue, were studied. In vitro experiments, looking at the mesenchymal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…seeded cell density, cell proliferation, ECM production, etc.) ( Grayson et al, 2008 ; Panseri et al, 2021 ). The effect of porosity on the permeability of the scaffold, which describes the amount of flow through the scaffold, can be calculated by the Kozeny-Carman Equation ( Eq.…”
Section: The Role Of Scaffold Pore Geometry On the Cell Micro-mechanical Environmentmentioning
confidence: 99%
“…seeded cell density, cell proliferation, ECM production, etc.) ( Grayson et al, 2008 ; Panseri et al, 2021 ). The effect of porosity on the permeability of the scaffold, which describes the amount of flow through the scaffold, can be calculated by the Kozeny-Carman Equation ( Eq.…”
Section: The Role Of Scaffold Pore Geometry On the Cell Micro-mechanical Environmentmentioning
confidence: 99%
“…A wide range of tasks related to the field of biomedical materials science includes the unresolved problem of effective implant osseointegration [1][2][3][4][5][6][7][8]. Currently known materials which can potentially be used as bone allografts have a number of disadvantages, such as reduced biocompatibility, allergic and toxic reactions [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Research from Panseri et.al. [42] has demonstrated that the combination of multi-scale structures with core-shell design of the scaffolds could successfully mimic the cortical bone structure. They have used human adipose-derived stem cells (hADSCs) cells as a very appropriate choice for autologous stem cells in order to boost bone regeneration.…”
Section: Introductionmentioning
confidence: 99%